Retinal Degenerative Diseases: Mechanisms and Experimental Therapy - Bowes Rickman, Catherine; LaVail, Matthew M.; Anderson, Robert E.; Grimm, Christian; Hollyfield, Joe; Ash, John (Advances in experimental medicine and biology, 2016)
Part I Age-Related Macular Degeneration (AMD) -- Apolipoprotein E Isoforms and AMD -- Role of Chemokines in Shaping Macrophage Activity in AMD -- Biology of p62/sequestosome-1 in Age-Related Macular Degeneration (AMD) -- Gene Structure of the 10q26 locus: A Clue to Cracking the ARMS2/HTRA1 Riddle? -- Conditional Induction of Oxidative Stress in RPE: A Mouse Model of Progressive Retinal Degeneration -- Therapeutic Approaches to Histone Reprogramming in Retinal Degeneration -- A Brief Discussion on Lipid Activated Nuclear Receptors and Their Potential Role in Regulating Microglia in Age-Related Macular Degeneration (AMD) -- Extracellular Matrix Alterations and Deposit Formation in AMD -- The NLRP3 Inflammasome and its Role in Age-related Macular Degeneration -- Oxidative Stress and the Nrf2 Anti-Oxidant Transcription Factor in Age-Related Macular Degeneration -- Aging Changes in Retinal Microglia and their Relevance to Age-related Retinal Disease -- VEGF-A and the NLRP3 Inflammasome in Age-Related Macular Degeneration -- Interrelation Between Oxidative Stress and Complement Activation in Models of Age-Related Macular Degeneration -- Gene-diet Interactions in Age-Related Macular Degeneration -- Challenges in the Development of Therapy for Dry Age-Related Macular Degeneration -- Nanoceria: A Potential Therapeutic for Dry AMD -- β-amyloidopathy in the Pathogenesis of Age-Related Macular Degeneration in Correlation with Neurodegenerative Diseases -- Part II Macular Dystrophies/Inherited Macular Degeneration -- Different Mutations in ELOVL4 Affect Very Long Chain Fatty Acid Biosynthesis to Cause Variable Neurological Disorders in Humans -- Mouse Models of Stargardt 3 Dominant Macular Degeneration -- Current Progress in Deciphering Importance of VLC-PUFA in the Retina -- Malattia Leventinese/Doyne Honeycomb Retinal Dystrophy: Similarities to Age-related Macular Degeneration and Potential Therapies -- Part III Inherited Retinal Degenerations -- Hsp90 as a Potential Therapeutic Target in Retinal Disease -- Leber Congenital Amaurosis: Genotypes and Retinal Structure Phenotypes -- A Chemical Mutagenesis Screen Identifies Mouse Models with ERG Defects -- Ablation of Chop Transiently Enhances Photoreceptor Survival But Does Not Prevent Retinal Degeneration in Transgenic Mice Expressing Human P23H Rhodopsin -- Identification of a Novel Gene on 10q22 Causing Autosomal Dominant Retinitis Pigmentosa (adRP) -- FAM161A and TTC8 Are Differentially Expressed in Non-allelelic Early Onset Retinal Degeneration -- Mutations in the Dynein1 Complex are Permissible for Basal Body Migration in Photoreceptors but Alter Rab6 Localization -- RDS Functional Domains and Dysfunction in Disease -- TULP1 Missense Mutations Induces the Endoplasmic Reticulum Unfolded Protein Response Stress Complex (ER-UPR) -- Understanding Cone Photoreceptor Cell Death in Achromatopsia -- Geranylgeranylacetone Suppresses N-methyl-N-nitrosourea-induced Photoreceptor Cell Loss in Mice -- My Retina Tracker™: An On-line International Registry for People Affected with Inherited Orphan Retinal Degenerative Diseases and their Genetic Relatives - A New Resource -- A Mini-Review: Animal Models of GUCY2D Leber Congenital Amaurosis (LCA1) -- A Comprehensive Review of Mutations in the MERTK Proto-oncogene -- Part IV In Vivo Imaging and Other Diagnostic Advances -- New Developments in Murine Imaging for Assessing Photoreceptor Degeneration In Vivo -- Reliability and repeatability of Cone Density Measurements in Patients with Congenital Achromatopsia -- Quantitative Autofluorescence in Best Vitelliform Macular Dystrophy: RPE Lipofuscin is Not Increased in Non-Lesion Areas of Retina -- Interpretation of Flood-Illuminated Adaptive Optics Images in Subjects with Retinitis Pigmentosa -- Intra-familial Similarity of Wide-Field Fundus Autofluorescence in Inherited Retinal Dystrophy -- Wide-Field Fundus Autofluorescence for Retinitis Pigmentosa and Cone/Cone-Rod Dystrophy.- The Development of a Cat Model of Retinal Detachment and Re-Attachment -- Part V Mechanisms of Degeneration -- The Role of X-Chromosome Inactivation in Retinal Development and Disease -- A Non-canonical Role for β-Secretase in the Retina -- The Consequences of Hypomorphic RPE65 for Rod and Cone Photoreceptors -- The Rate of Vitamin A Dimerization in Lipofuscinogenesis, Fundus Autofluorescence, Retinal Senescence and Degeneration -- Can Vitamin A be Improved to Prevent Blindness due to Age-Related Macular Degeneration, Stargardt Disease and Other Retinal Dystrophies? -- Class I Phosphoinositide 3-Kinase Exerts a Differential Role on Cell Survival and Cell Trafficking in Retina -- Cell Cycle Proteins and Retinal Degeneration: Evidences of New Potential Therapeutic Targets -- Neuronal Nitric Oxide Synthase as a Trigger of the N-methyl-N-nitrosourea-induced Photoreceptor Cell Death -- Molecular Principles for Decoding Homeostasis Disruptions in the Retinal Pigment Epithelium: Significance of Lipid Mediators to Retinal Degenerative Diseases -- Aging and Vision -- Part VI Neuroprotection, Small Molecules & Related Therapeutic Approaches -- The Potential Use of PGC-1α and PGC-1β to Protect the Retina by Stimulating Mitochondrial Repair -- Retinal Caveolin-1 Modulates Neuroprotective Signaling -- Photoreceptor Neuroprotection: Regulation of Akt activation through Serine/Threonine Phosphatases, PHLPP and PHLPPL -- The Role of AMPK pathway in Neuroprotection -- Tauroursodeoxycholic Acid Protects Retinal Function and Structure in rd1 -- Near-Infrared Photobiomodulation in Retinal Injury and Disease -- Exercise and Cyclic Light Preconditioning Protect Against Light-Induced Retinal Degeneration and Evoke Similar Gene Expression Patterns -- Small Molecules that Protect Mitochondrial Function from Metabolic Stress Decelerate Loss of Photoreceptor Cells in Murine Retinal Degeneration Models -- Histone Deacetylase: Therapeutic Targets in Retinal Degeneration -- Therapeutic Approach of Nanotechnology for Oxidative Stress Induced Ocular Neurodegenerative Diseases -- Transscleral Controlled Delivery of Geranylgeranylaceton Using a Polymeric Device Protects Rat Retina Against Light Injury -- Targeting the Proteostasis Network in Rhodopsin Retinitis Pigmentosa -- Part VII Gene Therapy & Antisense.- Gene Therapy for MERTK-Associated Retinal Degenerations -- Tamoxifen-containing Eye Drops Successfully Trigger Cre-mediated Recombination in the Entire Eye -- Distinct Expression Patterns of AAV8 Vectors with Broadly Active Promoters from Subretinal Injections of Neonatal Mouse Eyes at Two Different Ages -- Characterization of Ribozymes Targeting a Congenital Night Blindness Mutation in Rhodopsin -- Antisense Oligonucleotide Therapy for Inherited Retinal Dystrophies -- Functional Rescue of Retinal Degeneration-Associated Mutant RPE65 Proteins -- Evaluation of Ocular Gene Therapy in an Italian Patient Affected by Congenital Leber Amaurosis Type 2 Treated in Both Eyes -- Part VIII Stem Cells & Cell-based Therapies -- Regenerative Medicine: Solution in Sight -- Personalized Medicine: Cell and Gene Therapy Based on Patient-Specific iPSC-derived Retinal Pigment Epithelium Cells -- Human Retinal Pigment Epithelium Stem Cell (RPESC) -- Embryonic Stem Cell-Derived Microvesicles: Could They Be Used for Retinal Regeneration? -- Intravitreal Implantation of Genetically Modified Autologous Bone Marrow-Derived Stem Cells for Treating Retinal Disorders.- Gliosis Can Impede Integration Following Photoreceptor Transplantation into the Diseased Retina -- Interkinetic Nuclear Migration in the Regenerating Retina -- Part IX Photoreceptors & Inner Retina -- Use of a Machine Learning-Based High Content Analysis Approach to Identify Photoreceptor Neurite Promoting Molecules -- A Novel Approach to Identify Photoreceptor Compartment-Specific Tulp1 Binding Partners -- Thyroid Hormone Signaling and Cone Photoreceptor Viability -- In-Depth Functional Diagnostics of Mouse Models by Single-Flash and Flicker Electroretinograms without Adapting Background Illumination -- The Role of Intraflagellar Transport in the Photoreceptor Sensory Cilium -- Regulation of Retinal Development Via the Epigenetic Modification of Histone -- The Potential Role of Flavins and Retbindin in Retinal Function and Homeostasis -- Identification of Tyrosine O Sulfated Proteins in Cow Retina and the 661W Cell Line -- The Function of Arf-like Proteins ARL2 and ARL3 in Photoreceptors.-Characterization of Antibodies to Identify Cellular Expression of Dopamine -- Receptor 4 -- A Possible Role of Neuroglobin in the Retina After Optic Nerve Injury: A Comparative Study of Zebrafish and Mouse Retina -- JNK Inhibition Reduced Retinal Ganglion Cell Death After Ischemia/Reperfusion In Vivo and After Hypoxia In Vitro -- Cell Fate of Müller Cells During Photoreceptor Regeneration in an MNU-induced Retinal Degeneration Model of Zebrafish -- Polymodal Sensory Integration in Retinal Ganglion Cells -- Pigment Epithelium-derived Factor...